The Effect of Sterilization Time on the Chemical, Microbiological, and Heavy Metal Characteristics of Paniki Chickens Packed Canning Process - Rasulu, Hamidin; Husen, Janiah; Bahri, Syamsul; Wulansari, Angela; Mustafa, Ikrima M. Mustafa; Nurhikmat, Asep; Santi, Andi; Kiay, Nancy; Albaar, Nurjanna; Fatmawati, Mila; Ahmed A Mansour, Nabel (Indonesian Food Science and Technology Journal, 2024)
Traditional food is generally less popular with consumers, because apart from the taste being different from modern food, it causes traditional food to easily spoil. One of the traditional foods of North Maluku is panici chicken. This research aims to determine the effect of sterilization time on the chemical, microbiological and metal contamination characteristics of paniki chicken in canned packaging. The research design used was a linear regression method and a completely randomized design with 4 treatments and 3 replications. Treatments were sterilization time (W) (10, 15, 20, 25 minutes) with observation periods of 1, 2, and 3 months. The parameters studied were chemical, microbiological and metal contamination characteristics. The results of the research produced chemical properties including water content with 1 month storage 31.40–37.54%, 2 months 33.85–37.36%, 3 months 34.74–38.56%, ash content with 1 month storage 1 .22–1.61%, 2 months 1.5–1.70%, 3 months 1.56–1.78%, fat content with storage 1 month 11.2–13.74%, 2 months 12.20 –13.95%, 3 months 13.68–14.67%, protein content with 1 month storage 20.80–23.65%, 2 months 22.22–23.61%, 3 months 23.00–24 .55%, carbohydrates with 1 month storage 29.01–33.27%, 2 months 29.79–33.99%, 3 months 31.36–35.16%, total energy with 1 month storage 839.12– 688.59 KCal/100g, 2 months 700.34–734.46 KCal/100g, 3 months 630.01–699.39 KCal/100g, TBA with 1 month storage 0.12–0.21%, 2 months 0.16 –0.25%, 3 months 0.19–0.40%, microbiology includes ALT with 1 month storage 1x101 CFU/g, dua bulan 1x101 CFU/g, three months 1x101 CFU/g.